2019
DOI: 10.1111/pbr.12739
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of vitamin E content in rice (Oryza sativa) grains using recombinant inbred lines derived from a cross between 'Zhenshan97B' and 'Nanyangzhan'

Abstract: Vitamin E (VE) is an important nutritional trait in rice grains. In order to dissect the genetic basis underlying VE content, a recombinant inbred lines population derived from 'Zhenshan 97B' and 'Nanyangzhan' was used for quantitative trait locus (QTL) analysis. Totally, 29 QTLs for six VE traits were identified in 2 consecutive years. Among those, five QTLs repeatedly detected in two years formed a cluster on chromosome 2, which was responsible for all five VE isomers. OsγTMT, the gene encoding γ‐tocopherol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Zhan et al (2019) grew three RIL populations (n = 170-188 lines) from the crosses of Zong3 by Yu8701 (ZXY), K22XCI7, and B73 by BY804 (BXB) in two environments in China and genotyped them with 50 k SNPs. They used CIM of WinQTLCart2.5 for QTL analysis and identified one major QTL that controls seed γ-tocopherol and total tocopherol (qVE5) on chromosome 5 [48]. The major QTL qVE5 was also identified in a previous study [44] and confirmed here in these three RIL populations [49].…”
Section: Seed Tocopherol Candidate Genessupporting
confidence: 63%
See 1 more Smart Citation
“…Zhan et al (2019) grew three RIL populations (n = 170-188 lines) from the crosses of Zong3 by Yu8701 (ZXY), K22XCI7, and B73 by BY804 (BXB) in two environments in China and genotyped them with 50 k SNPs. They used CIM of WinQTLCart2.5 for QTL analysis and identified one major QTL that controls seed γ-tocopherol and total tocopherol (qVE5) on chromosome 5 [48]. The major QTL qVE5 was also identified in a previous study [44] and confirmed here in these three RIL populations [49].…”
Section: Seed Tocopherol Candidate Genessupporting
confidence: 63%
“…Wang et al (2018) identified 41 QTL and 151 SNPs associated with seed tocopherol-related traits and many candidate genes within these QTL regions, including GRMZM2G436226 that encodes a Zinc finger CCCH domain-containing protein on chromosome 1, GRMZM2G055752 that encodes a DNA topoisomerase and GRMZM2G079236 that encodes a Acyl-CoA synthetase long-chain family member on chromosome 2, GRMZM2G170013 that encodes a chlorophyll b reductase NYC1 on chromosome 3, GRMZM5G892742 that encodes a DNAJ-related chaperone protein and GRMZM2G150714 that encodes a putative leucine-rich repeat receptor-like protein kinase family protein on chromosome 4, GRMZM2G035213 that encodes a γ-tocopherol methyltransferase (VTE4) and GRMZM2G024739 that encodes a Cryptochrome-1 (CRY1) on chromosome 5, GRMZM2G127299 that encodes a transcription factor GTE8 and GR-MZM2G146190 that encodes a peptidyl-prolyl cis-trans isomerase (CYP59) on chromosome 6, GRMZM2G003022 that encodes a COPII vesicle coat on chromosome 8, GRMZM5G818232 that encodes a Clavata3/esr-related16 on chromosome 9, GRMZM2G004534 that encodes a pyruvate kinase 2 on chromosome 10, and many other genes (Table S1) [44]. Zhang et al (2019) created transgenic seeds of maize and Arabidopsis thaliana and overexpressed the gene ZmTMT (VTE4) that encodes γ-tocopherol methyltransferase in those seeds and observed a 4-5-fold increase in α-tocopherol content in Arabidopsis and 6.5-fold increase in maize transgenic plants while the (α/γ)-tocopherol ratio increased by 15-fold and 17-fold, respectively, which proves that increasing tocopherol content in corn is feasible [48]. Zhan et al (2019) grew three RIL populations (n = 170-188 lines) from the crosses of Zong3 by Yu8701 (ZXY), K22XCI7, and B73 by BY804 (BXB) in two environments in China and genotyped them with 50 k SNPs.…”
Section: Seed Tocopherol Candidate Genesmentioning
confidence: 99%
“…Indeed, for instance, wheat germ oils contain the highest concentration of vitamin E of all species tested ( Trela and Szymańska, 2019 ). Although substantial efforts have been made in elucidating the metabolic pathway of vitamin metabolism in other crops ( Zhou et al., 2012 ; Quadrana et al., 2014 ; Liu et al., 2017 ; Wang et al., 2018 ; Schuy et al., 2019 ; Zhang et al., 2019 ), less has been achieved in wheat ( Li et al., 2018b ; Watkins et al., 2019 ). In view of this, key candidate genes could be swiftly selected and validated through multi-omics approaches including metabolomics, providing molecular resources for breeding wheat to be a more nutritional food.…”
Section: Breeding Wheat To Be a Better Crop Assisted By Metabolomics Approaches As Indication Prediction And Navigation Toolsmentioning
confidence: 99%
“…In addition, there are apparent variations in the contents of these compounds among rice cultivars (Bergman & Xu, 2003;Heineman et al, 2008;Huang & Ng, 2011;Kato et al, 2017;Ng et al, 2013). Several quantitative trait loci have been identified for the contents of gOZ (Kato et al, 2017;Nakano et al, 2018) and vitamin E derivatives (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%